Risk of gentamicin toxicity in neonates treated for possible severe bacterial infection in low‐ and middle‐income countries: Systematic Review. Issue 12 (23rd October 2015) - Musiime, Grace M.; Seale, Anna C.; Moxon, Sarah G.; Lawn, Joy E.
Abstract: Objectives: To assess the risk of gentamicin toxicity and potential number of neonates exposed annually to this risk, through treatment with WHO‐recommended first‐line antibiotics (gentamicin with penicillin) for the 6.9 million neonates with possible serious bacterial infection (PSBI). Methods: Systematic literature review and assessment of the evidence using Cochrane and GRADE criteria. Meta‐analysis was undertaken for pooled estimates where appropriate. Results: Eleven studies (946 neonates) were included (nine randomised controlled trials and two prospective cohort studies). Six trials reported consistently measured ototoxicity outcomes in neonates treated with gentamicin, and the pooled estimate for hearing loss was 3% (95% CI 0–7%). Nephrotoxicity could not be assessed due to variation in case definitions used. Estimates of the number of neonates potentially affected by gentamicin toxicity were not undertaken due to insufficient data. Conclusion: Given wider scale‐up of outpatient‐based and lower‐level treatment of PSBI, improved data are essential to better assess the risks from neonatal gentamicin treatment without assessment of blood levels, to maximise benefit and reduce harm.